Effectiveness of Ergonomic Training in Reducing Musculoskeletal Disorders Among Farmers: An Agricultural Nursing Program - Nadia Sintia Wardany; Slamet Rohaedi; Irma Darmawati; Ridha Wahdini; Agni Laili Perdani (Jurnal Keperawatan Komprehensif (Comprehensive Nursing Journal), 2025)
Background : Musculoskeletal disorders (MSDs) represent a major occupational health concern among agricultural workers in Indonesia. These conditions commonly arise from repetitive workloads, awkward or non-ergonomic body positions, and insufficient understanding of ergonomic practices. As a result, farmers may experience ongoing discomfort, reduced work capacity, and a decline in overall well-being. Objective : The purpose of this study was to assess the effectiveness of an Ergonomics Exercise Program (EEP) in alleviating musculoskeletal complaints among farmers. Methods : This study applied a pre- and post-intervention design involving 85 farmers. Symptoms related to musculoskeletal disorders were evaluated before and after the intervention using the Visual Analog Scale (VAS) and the Nordic Body Map (NBM). The Ergonomics Exercise Program was carried out over a two-week period, with participants performing 10-minute exercise sessions each day prior to starting work. The intervention focused on flexibility training, strengthening of core muscles, and correction of working posture. Changes in MSD symptoms were analyzed statistically to determine the effect of the program. Results : Before the intervention, 54% of participants reported mild pain, while 46% experienced moderate pain levels. The most commonly affected body areas included the calves (62.3%), lower back (45.8%), arms (40%), and shoulders (28.2%). Following the implementation of the Ergonomics Exercise Program, a statistically significant reduction in musculoskeletal complaints was observed (p < 0.05), particularly in the lower back, shoulders, and calves. Conclusion : The findings indicate that the Ergonomics Exercise Program effectively reduced musculoskeletal disorder symptoms among farmers. Incorporating ergonomics-based exercise routines into agricultural nursing and occupational health initiatives may offer a practical and sustainable approach to improving worker health and preventing MSDs in rural farming populations in Indonesia.